Mast Cell, the Neglected Member of the Tumor Microenvironment: Role in Breast Cancer - Aponte-López, Angélica (J Immunol Res, 2018)
Mast cells are unique tissue-resident immune cells that secrete a diverse array of biologically active compounds that can stimulate, modulate, or suppress the immune response. Although mounting evidence supports that mast cells are consistently infiltrating tumors, their role as either a driving or an opposite force for cancer progression is still controversial. Particularly, in breast cancer, their function is still under discussion. While some studies have shown a protective role, recent evidence indicates that mast cells enhance blood and lymphatic vessel formation. Interestingly, one of the most important components of the mast cell cargo, the serine protease tryptase, is a potent angiogenic factor, and elevated serum tryptase levels correlate with bad prognosis in breast cancer patients. Likewise, histamine is known to induce tumor cell proliferation and tumor growth. In agreement, mast cell depletion reduces the size of mammary tumors and metastasis in murine models that spontaneously develop breast cancer. In this review, we will discuss the evidence supporting protumoral and antitumoral roles of mast cells, emphasizing recent findings placing mast cells as important drivers of tumor progression, as well as the potential use of these cells or their mediators as therapeutic targets.